Effects of Cage Change on the Production of Sprague Dawley Rats - León, Edwin; Reyes, Ledis; Pacheco, Luis; Fátima (Spei Domus, 2013)
Olfactory signals that enable mother rats to communicate with their young are critical. More frequent cleaning of primary enclosures eliminates olfactory signals that affect the number of pups weaned. To measure the influence of changes on the production of rats of the Sprague Dawley strain, it was decided to change the cages of females once a week throughout the production cycle (from mating until weaning) (28 females) for the experimental group, and twice a week (28 females) for the control group because this is the usual system for changing them. The minimum and maximum temperature and humidity values of the secondary enclosure were also recorded to compare their influence on changes in the animals; this was then compared to the effect on the number of births or the change in the system (8 females in each group). The average number of pups born to mother rats was compared using hypothesis contrasting and the effects of temperature, humidity and a second delivery were analyzed using logistical regression. It was found that when performing hypothesis testing, there was no statistically significant difference in the number of animals produced at weaning due to one change or two changes. And when compared to the other factors, it was found that the number of females produced in the logistical regression was more significant than the modification in changing the animals’ cages.